STUDENTS' LEARNING RESULTS OF IPS CLASS VIII.3 SMP NEGERI 1 SETU THROUGH DISCOVERY LEARNING METHOD - Nuryanah Nuryanah; Mahatma Mahatma (Universitas Panca Sakti Bekasi, 2022)
The low student learning outcomes are caused by the use of conventional learning models that cause boredom and students are not active in learning activities in class. This study aims to analyze learning based on the Discovery Learning Method on the social studies learning outcomes of class VIII.3 students of SMP NEGERI 1 Setu. This study aims to explain the improvement of student learning outcomes. This research is a classroom action research. The subjects of this study were students of class VIII.3 SMP NEGERI 1 SETU with the discovery learning method, totaling 36 students. This Classroom Action Research was conducted in 2 stages, and at each stage includes 4 stages, namely: Planning, Action, Observation and Reflection. The data collected in this study is the data of students' social studies learning outcomes. The method used to collect data is the Test Method. This test technique is carried out in the activity of giving questions in the form of PG (multiple choice) in order to determine the power of students after being given the action. Before Cycles 1 and 2, students' pre-cycle scores were obtained from students' initial test scores before Cycles 1 and 2. The results obtained by students were 36 students with a minimum score of 55, a maximum score of 80, and an average of 65.00. Only 15 students (41%) reached the KKM. So that 21 students (59%) did not reach the KKM. After the first cycle was implemented, the highest score was 85, the lowest score was 60, and the average score was 75.50. There were 23 (58%) students, who did not reach the KKM there were 13 (42%) students. After two cycles, Cycle 2 carried out a written social studies subject with the following results: The highest score was 95, the lowest score was 65, and the average was 84.50. There were 31 students (86%), and the students who did not complete the Minimum Completeness Criteria (KKM) were 5 students (14%). Data acquisition technology through observation and testing to measure social studies learning outcomes. Based on the results of research and data analysis, it was concluded that the use of discovery learning methods had an effect on student learning outcomes in class VIII.3 SMP NEGERI 1 SETU.